Comportamiento del índice de temperatura-humedad en la cabecera del río carrizal para la identificación de periodos de estrés térmico en bovinos - Custodio Toapanta, Mishell Pamela (2026)
The behavior of the temperature-humidity index (THI) in cattle was evaluated using data from meteorological stations at the headwaters of the Carrizal River in the province of Manabí. Ambient temperature and relative humidity were analyzed, and the THI was calculated both monthly and hourly. The data did not meet the assumptions of normality and homoscedasticity, so the Kruskal-Wallis test was applied. The results showed highly significant differences (p<0.001) among the stations, months, and hectares evaluated, highlighting that the Tosagua meteorological station recorded the highest temperatures (26.81 ± 3.20 °C) and the highest THI (77.61 ± 3.75 units), while relative humidity was lower (80.86 ± 11.40 %). An antagonism between temperature and humidity was observed, and THI values exceeded the critical threshold of 72 units, indicating a risk of heat stress in cattle. Additionally, seasonal patterns were identified, with higher temperatures (28.09 ± 3.46 °C) and THI (79.90 ± 3.65 units) in March and maximum humidity in January (88.47 ± 10.16 %). Hourly, the peak ambient temperature and THI were recorded at 12:00 PM (30.91 ± 2.41 °C and 82.24 ± 2.42 units, respectively), while humidity was lower (68.08 ± 9.81 %). It is concluded that the THI exceeded 72 units in the influence area of the Carrizal River headwaters, negatively affecting the health, production, and reproduction of cattle with a high percentage of Bos taurus crossbreeding.